Hume's skepticism in the Treatise of human nature - Fogelin, Robert J. (Routledge library editions. 18th century philosophy, 2019)
This work, first published in 1985, offers a general interpretation of Hume's Treatise of Human Nature. Most Hume scholarship has either neglected or downplayed an important aspect of Hume's position -- his scepticism. This book puts that right, examining in close detail the sceptical arguments in Hume's philosophy.